Degranulation patterns of eosinophil granulocytes as determinants of eosinophil driven disease. Issue 5 (1st May 2001) - Erjefält, J S; Greiff, L; Andersson, M; Ädelroth, E; Jeffery, P K; Persson, C G A
Abstract : BACKGROUND: Degranulation of eosinophils in target tissues is considered a key pathogenic event in major chronic eosinophilic diseases. However, because of a lack of appropriate methods, little is known about degranulation of eosinophils in common eosinophilic diseases. METHODS: Using transmission electron microscopic (TEM) analysis, a novel approach has been devised and validated to quantify eosinophil degranulation in human tissues (assessed in individual cells as percentage granules with structural signs of protein release). Biopsy specimens from patients with inflammatory bowel disease, allergic rhinitis, asthma, and nasal polyposis were evaluated. RESULTS: All conditions displayed a similar degree of local tissue eosinophilia, with no differences being observed in eosinophil numbers in the airway mucosa of patients with airway diseases and the colonic mucosa of those with inflammatory bowel disease (IBD). In contrast, marked differences in the mean (SE) extent of eosinophil degranulation were observed between the patient groups; IBD 9.3 (1.4)% altered granules, artificial and natural allergen challenge induced allergic rhinitis 67.8 (6.8)% and 86.6 (3.0)%, respectively, asthma 18.1 (2)%, and nasal polyposis 46.6 (7.6)%. CONCLUSIONS: This study provides the first quantitative data which show that different eosinophilic conditions, despite having similar numbers of tissue eosinophils, may exhibit markedly different degranulation patterns. The present assessment of piecemeal degranulation would thus make it possible to delineate the conditions under which eosinophils are likely to contribute to disease processes. This novel type of analysis may also guide and validate anti-eosinophilic treatment options.